Application Of Local Functions In Culture Melayu Arabic Of Jambi Seberang Communities As A History Learning Module - Apdelmi Apdelmi; Reka Seprina (Universitas Negeri Padang, 2019)
In essence, culture has values that are capable of being inherited and carried out along with the development of society. In carrying out our daily lives we cannot be separated from cultural elements, every thing we do and we do in life is greatly influenced by local culture. Culture is also used as a guide for making decisions in the fields of social, legal, economic and inherited through communication from one generation to the next, so that generations inherited have the toughness in living their lives. As stated by Geertz in (Rusdi Yunus, 2014: 1) that culture is a pattern of meaning manifested in symbols and passed down from generation to generation. In other words, culture is the work of humans who are able to produce and develop human knowledge and attitudes towards life that are inherited through communication and learning.